The United States, Canada, and the new international economic order - Laszlo, Ervin; Kurtzman, Joel.; United Nations Institute for Training and Research; Centro de Estudios Económicos y Sociales del Tercer Mundo (New York : Published for UNITAR and the Center for Economic and Social Studies of the Third World (CEESTEM) [by] Pergamon Press, 1979)
The UNITAR/CEESTEM Policy Studies on New International Economic Order examines obstacles as well as opportunities associated with current efforts to create a new and more equitable world economic order. This focuses on the United States and Canada and examines how diverse segments of the North American population respond to demands for a new international economic order, how they evaluate attempts in this area.
"A volume in the New international economic order (NIEO) library."
Includes bibliographical references and index.
usc 11/04/2018
Loans
Keywords: International economic relations; United States; Canada